(untitled) (Journal of the Bangladesh Agricultural University, 2025)
Rice is the staple food for about half of the world’s population and requires extensive urea fertilization. However, urea is prone to multifaceted losses, leading to environmental pollution. A pot experiment was conducted to investigate the suitability of using chitin nanofiber (CNF) on the growth and yield of BRRI dhan28. The experiment was laid out in a completely randomized design (CRD) with five treatments, e.g., 0.4% CNF, urea (recommended dose), CNF: urea (50:50), CNF: urea (75:25), and water (control) and replicated seven times. Among the treatments, CNF-urea (50/50) resulted in statistically similar plant height, tiller number, panicle length, and effective number of panicles with urea. CNF-urea (50/50) also had lower unfilled spikelets than the recommended dose of urea. Moreover, grain yield and harvest index were numerically higher for CNF-urea (50/50) than the recommended dose of urea. Therefore, CNF-urea (50/50) may produce a rice yield similar to urea, suggesting that half of the urea-nitrogen can be supplemented by CNF without significant yield loss of rice (BRRI dhan28). However, further experiments should be conducted in different seasons and in multilocation to get a final recommendation. J Bangladesh Agril Univ 23(3): 287–295, 2025